Leaping the hurdles in developing regenerative treatments for the intervertebral disc from preclinical to clinical. Issue 3 (2nd August 2018) - Thorpe, Abbey A.; Bach, Frances C.; Tryfonidou, Marianna A.; Le Maitre, Christine L.; Mwale, Fackson; Diwan, Ashish D.; Ito, Keita
Abstract : Chronic back and neck pain is a prevalent disability, often caused by degeneration of the intervertebral disc. Because current treatments for this condition are less than satisfactory, a great deal of effort is being applied to develop new solutions, including regenerative strategies. However, the path from initial promising idea to clinical use is fraught with many hurdles to overcome. Many of the keys to success are not necessarily linked to science or innovation. Successful translation to clinic will also rely on planning and awareness of the hurdles. It will be essential to plan your entire path to clinic from the outset and to do this with a multidisciplinary team. Take advice early on regulatory aspects and focus on generating the proof required to satisfy regulatory approval. Scientific demonstration and societal benefits are important, but translation cannot occur without involving commercial parties, which are instrumental to support expensive clinical trials. This will only be possible when intellectual property can be protected sufficiently to support a business model. In this manner, commercial, societal, medical, and scientific partners can work together to ultimately improve patient health. Based on literature surveys and experiences of the co‐authors, this opinion paper presents this pathway, highlights the most prominent issues and hopefully will aid in your own translational endeavors. Abstract : Much effort is being applied to develop regenerative strategies to treat chronic back and neck pain caused by intervertebral disc degeneration. This path from initial promising idea to clinical use is fraught with many hurdles to overcome. Based on literature surveys and experiences of the co‐authors, this opinion paper presents this pathway, highlights the most prominent issues and hopefully will aid in your own translational endeavors. CMC = Chemical and Manufacturing Control, GMP = Good Manufacturing Practice, IND = Investigational New Drug, IFU = Indication for Use, IRB = Institutional Review Board.